2008
DOI: 10.1103/physrevd.78.104006
|View full text |Cite
|
Sign up to set email alerts
|

Evolving Lorentzian wormholes supported by phantom matter with constant state parameters

Abstract: In this paper we study the possibility of sustaining an evolving wormhole via exotic matter made out of phantom energy. We show that this exotic source can support the existence of evolving wormhole spacetimes. Explicitly, a family of evolving Lorentzian wormholes conformally related to another family of zero-tidal force static wormhole geometries is found in Einstein gravity. Contrary to the standard wormhole approach, where first a convenient geometry is fixed and then the matter distribution is derived, we … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 46 publications
2
47
0
Order By: Relevance
“…Notice that for an anisotropic matter with ω r < −1 we have that ρ in (t, r) > 0, while for an anisotropic matter with ω r > 0 we have that ρ in (t, r) < 0. For ρ(t) = Λ = 0 the shape of the wormhole expands with constant velocity [11]. In the presence of a cosmological constant with ρ in (t, r) = 0 the wormhole configurations have an accelerated expansion (contraction) [12].…”
Section: Expanding Wormhole Universesmentioning
confidence: 99%
See 2 more Smart Citations
“…Notice that for an anisotropic matter with ω r < −1 we have that ρ in (t, r) > 0, while for an anisotropic matter with ω r > 0 we have that ρ in (t, r) < 0. For ρ(t) = Λ = 0 the shape of the wormhole expands with constant velocity [11]. In the presence of a cosmological constant with ρ in (t, r) = 0 the wormhole configurations have an accelerated expansion (contraction) [12].…”
Section: Expanding Wormhole Universesmentioning
confidence: 99%
“…Notice that if ρ(t) = Λ = 0 the space expands with constant velocity [11], and for ρ(t) = 0 and Λ = 0 the rate of expansion is determined by the cosmological constant [12].…”
Section: Field Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The functions b(r) and Φ(t, r) are called the shape function and redshift function respectively. Earlier the evolving wormholes have been studied with time-independent redshift function Φ(r) [29]. If a(t) → constant and Φ(t, r) → Φ(r), then the static MT wormhole can be obtained whereas for b(r) → kr 3 and Φ(t, r) → constant, Eq (1) reduces to standard FRW metric.…”
Section: Basic Equationsmentioning
confidence: 99%
“…Arellano & Lobo [27] found contracting wormhole solutions within non-linear electrodynamics. Cataldo et al discussed the construction of evolving wormholes using phantom energy [28,29] and more recently using the cosmological constant [30]. Farooq et al [31] showed that the field equations of a (2+1)-dimensional evolving wormhole can be recast into first law of thermodynamics.…”
Section: Introductionmentioning
confidence: 99%